Application of Inorganic Fertilizers and Organic Manures on the Production of Autotrophic Plankton in Madhupur Tract Soil Contained Miniature Tank - Huda, ME; Nabi, MR (Journal of Environmental Science and Natural Resources, 2017)
Appropriate fertilizer and their impact on physico-chemical parameters of water and productivity is very important for aquaculture and ecology. Optimum fertilizer dose can help in fish farmer as well as aquaculture sector. From the study it was found that the total physicochemical parameters of water were suitable for aquaculture, drinking water, irrigation and domestic use. The average water temperature was 26.45±2.75oC; 26.50±3.24oC; 25.83±4.08oC; 26.57±3.02oC and 26.53±2.93oC for MCRT-1 to 5 gradually. Water pH in an average was 7.37±0.61; 7.44±0.55; 7.25±0.58; 7.33±0.54 and 7.47±0.49 for Minature Circular Research Tank (MCRT)-1 to 5 respectively. Average water DO were 6.98±1.05 mgl-1; 6.75±1.53 mgl-1; 6.90±1.64 mgl-1; 6.59±1.19mgl-1 and 6.77±1.60mgl-1 for MCRT-1 to 5 respectively. Average water hardness were 71.88 ± 20.47 mgl-1; 60.5 ±2 1.25 mgl-1; 83.38 ± 23.39 mgl-1; 59.13 ± 25.57 mgl-1 and 52.63 ± 7.92 mgl-1 for MCRT-1 to 5 gradually. Average water total phosphorus were 0.77 ± 0.18 mgl-1; 0.83 ± 0.19 mgl-1; 0.78 ± 0.21 mgl-1; 0.84 ± 0.17 mgl-1 and 0.84 ± 0.16 mgl-1 for MCRT-1 to 5 gradually. From planktonic study it was found that the highest phytoplankton and Zooplankton were in MCRT-3. Phytoplanktons were under 27 no. of genera. Their groups were Cyanophyceae, Chlorophyceae, Bacillariophyceae, Euglenophyceae and Hepatecae.Zooplankton were five major taxa and they were Protozoa, Rotifera, Cladocera, Copepod and Ostracoda respectively. J. Environ. Sci. & Natural Resources, 10(1): 9-14 2017